Interaksi Simbolik Pengurus Pondok Pesantren dalam Memperkuat Akhlak dan Disiplin Santri - Febriany, Febriany; Adah, Nilna Alfaizah; Sofiatun, Siti (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2024)
This article examines the application of symbolic interaction theory by Pondok Pesantren administrators in the context of strengthening the morals and discipline of santri. Pondok Pesantren, as a traditional educational institution in Indonesia, plays a central role in shaping the character and morality of santri through various religious practices and social traditions. A qualitative approach was used in this study, focusing on data collection through in-depth interviews with administrators and participatory observation of daily activities in Pondok Pesantren. The results of the study show that Pondok Pesantren administrators actively use religious symbols, such as exemplary behavior, spiritual advice, and participation in religious rituals, as the main strategy to strengthen the morals of santri. Exemplary behavior shown by administrators becomes a model followed by santri in various aspects of daily life, while spiritual advice provides in-depth moral and ethical guidance. The participation of santri in religious activities such as congregational prayers, yellow book studies, and social activities also helps in the formation of discipline and compliance with religious values.